Megagametophyte maturation dynamics and flavonol changes during Arbutus unedo flower development - D’Agostino, Alessia; Di Marco, Gabriele; Canini, Antonella; Gismondi, Angelo (Frontiers in Plant Science, 2025)
The flowering rhythm of Arbutus unedo L. (strawberry tree) is unusually prolonged and remains largely unexplored. Thus, this study characterizes its floral development through seven defined stages (St1-St7), from meristematic buds to anthesis. Histological analyses revealed that anther differentiation occurred earlier than ovule development, which displayed a prolonged apparent slowdown. To understand whether phytochemicals could play a signaling role in this context, due to their potential effects on hormones, proteins and DNA, total and specific quantitation of these compounds was performed by spectrophotometry and targeted (HPLC-DAD) and untargeted (GC-MS) metabolomic approaches. A general decline in secondary metabolite levels was observed from St1 to St7, except for flavonols, which exhibited a non-linear accumulation pattern. These findings were corroborated by principal component analysis and qPCR assays of genes involved in phenylpropanoid and flavonoid biosynthesis. Fluorescence histochemistry demonstrated that flavonols (kaempferol and quercetin) were synthesized with a stage- and tissue-specific localization, particularly at St2, St4, and St7, and accumulated mainly in the epidermis, pollen, and ovules. Their subcellular localization varied across stages, with notable nuclear accumulation in ovary and ovule tissues, suggesting a potential role in transcriptional regulation. In conclusion, the developmental dynamics of the megagametophyte and the spatiotemporal distribution of flavonols seem to influence flower maturation in A. unedo, indicating a possible regulatory function for these compounds beyond their conventional roles.